2013
DOI: 10.1038/modpathol.2012.133
|View full text |Cite
|
Sign up to set email alerts
|

The cancer-testis antigen NY-ESO-1 is highly expressed in myxoid and round cell subset of liposarcomas

Abstract: Liposarcomas are a heterogenous group of fat-derived sarcomas, and surgery with or without chemoradiation therapy remains the main stay of treatment. NY-ESO-1 is a cancer-testis antigen expressed in various cancers where it can induce both cellular and humoral immunity. Immunotherapy has shown promise in clinical trials involving NY-ESO-1-expressing tumors. Gene expression studies have shown upregulation of the gene for NY-ESO-1, CTAG1B, in myxoid and round cell liposarcomas. Herein, we evaluated the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 24 publications
5
45
1
1
Order By: Relevance
“…In our previous study, we reported that 7/8 (88%) and 16/18 (89%) myxoid and round cell liposarcomas expressed CTAG1B and NY-ESO-1 by quantitative real-time PCR and immunohistochemistry, respectively. 12 We also noted variable positive staining in a subset of pleomorphic liposarcomas (3/6) and an instance of strong, diffuse staining in dedifferentiated liposarcoma (1/10). Pollack et al 11 also reported NY-ESO-1 expression in 25/25 (100%) myxoid and round cell liposarcomas evaluated by immunohistochemistry and quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we reported that 7/8 (88%) and 16/18 (89%) myxoid and round cell liposarcomas expressed CTAG1B and NY-ESO-1 by quantitative real-time PCR and immunohistochemistry, respectively. 12 We also noted variable positive staining in a subset of pleomorphic liposarcomas (3/6) and an instance of strong, diffuse staining in dedifferentiated liposarcoma (1/10). Pollack et al 11 also reported NY-ESO-1 expression in 25/25 (100%) myxoid and round cell liposarcomas evaluated by immunohistochemistry and quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Both reports describe NY-ESO-1 expression as predominantly homogenous, which is notable given that cancer testis antigens usually demonstrate a heterogeneous staining pattern within a particular tumor. 5,11,12,26 In addition to possibly enabling an enhanced response to cancer testis antigen-directed immunotherapy, diffuse staining by NY-ESO-1 increases its appeal as an immunohistochemical marker of myxoid and round cell liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported NY-ESO-1 expression in an especially large proportion of myxoid liposarcomas and synovial sarcomas. 2,[6][7][8][9] These studies also revealed the absence of NY-ESO-1 expression in their histologic mimics such as myxoma, myxofibrosarcoma, extraskeletal myxoid chondrosarcoma, and lowgrade fibromyxoid sarcoma, and concluded that immunohistochemical staining of NY-ESO-1 is useful not only for candidate selection in immunotherapy, but also for histologic differential diagnosis. A limitation of these previous studies is that the sample sizes were too small to be conclusive and lacked independent external validation.…”
mentioning
confidence: 83%